The Impact of Personal and/or Close Relationship Experience on Memorable Messages about Breast Cancer and the Perceived Speech Acts of the Sender - Smith, Sandi W. (2009)
BACKGROUND: Memorable messages and their speech acts (purposes of the messages) can promote protection against breast cancer and guide health behaviors. METHODS: Participants reported their personal, friends’, and relatives’ experiences with breast cancer and a memorable message about breast cancer if one came to mind. Those with a memorable message reported its perceived speech acts. RESULTS: Individuals who had personal and friend or relative experience with breast cancer were significantly more likely to recall memorable messages than other respondents. The most frequently perceived speech acts were providing facts, providing advice, and giving hope. CONCLUSION: This information should be used to form messages in future breast cancer protection campaigns.